Organizational ambidexterity: a critical review and development of a project focused definition - Petro, Yacoub; Ojiako, Udechukwu; Williams, Terry; Marshall, Alasdair (Journal of Management in Engineering, 2019)
The objective of this paper is to explore a project-focused understanding of contemporary organizational ambidexterity literature. As part of this process, a taxonomical analysis of the elements and components of the concept of organizational ambidexterity is undertaken. Findings suggest that a project-focused notion of organizational ambidexterity involves different levels, dimensions, and mechanisms. The predominant contribution of this study resides within the taxonomy study, which provides a platform for a more holistic understanding of organizational ambidexterity as a multifaceted concept applicable to the project management discipline.